ASME x IG: The Cover as Content and Compositional Mechanism of the Social Media Post - Viñas Limonchi, Manuel; Fernández Álvarez, Lony (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Introduction: In 2005, the American Society of Magazine Editors (ASME) selected the forty most iconic magazine covers of the last four decades. Among the selected, leading publications such as Time and Esquire have, since their inception, created covers that surpass the boundaries of press design. Methodology: A content analysis is proposed, focusing on the compositional attributes present in these forty covers, interpreted as a paradigmatic resource and constructive elements of an Instagram post. Results: While the image remains unchanged in the post, the summary texts are positioned beneath it, serving as a lead, and the publication’s visual identity is repositioned to the beginning of the reading path. Discussion: The graphic plasticity and informational dimension of the magazine cover transcend its original compositional framework, influencing the layout configuration of the post itself.